Synergistic Effects of Prebiotics and Acidifiers in Broiler Chicks: A Sustainable Alternative to Antibiotics - Harendra Singh Rajoriya (The Indian Journal of Animal Sciences, 2026)
This study evaluated effect of prebiotics (fructo-oligosaccharides) and acidifiers as dietary supplementation. Experimental trial involved 120 one-day-old chicks fed different dietary treatments for the duration of 42-days.The birds were randomly divided into four groups (C, T1, T2, T3; 30 birds each). Group C (control) received standard broiler mash, T1 received mash with prebiotics (0.5% for 0–3 weeks, 0.25% for 4–6 weeks), T2 received acidifiers at same supplementation levels and T3 received a 1:1 combination of prebiotics and acidifiers at same levels. Study revealed significant improvements (P<0.01) in carcass traits, including dressing percentage, eviscerated weight and giblet yield, with T3 group outperforming others. Morphometric analysis showed increased villus height and width, along with reduced crypt depth in T3 group, indicating improved intestinal health. Improvements in dry matter metabolizability and nitrogen balance were also highest in T3 group, reflecting better nutrient utilization. Mortality rates were reduced in supplemented groups, with T1, T2 and T3 showing improved survival compared to control. Furthermore, economic analysis highlighted higher net profit in T3 group, emphasizing cost-effectiveness of combined supplementation. Findings of the trial accounts the favourable synergistic effect of combining prebiotics and acidifiers by improving growth performance, intestinal health and carcass characteristics, while also reducing mortality and boosting overall profitability. Results support use of prebiotic-acidifier combinations as sustainable alternatives to antibiotic growth promoters, offering viable strategy to optimize broiler production.